Study of the Importance of Lighting in Promoting Nightlife of Urban Spaces Case Study : Traditional neighborhood of Maghsoudieh Tabriz - saeedeh feizi; mostafa basiri (تحقیقات کاربردی علوم جغرافیایی)
The concept of the city's landscape is connected with the objectivity and subjectivity of that city. Therefore, in order to manage this concept at night, in addition to functional-physical manifestations of the city, we should focus on the perceptual issues of citizens, which may have roots in their ancient identity, religion and customs. By accepting this hypothesis, a suitable model for night-time urban landscape management should be considered as a model that reveals both the physical and functional aesthetics of the city, as well as the perceptual and psychological components of the citizens from the night view. Nowadays, with the expansion of night life, the concepts of the quality of the location of urban landscapes at night has became as important as day. The aim of this study is to evaluate the relationship between lighting and the sense of dependency that is one of the key factors in location's quality and the role of new lighting technologies in promoting the Social-physical concept of sense of dependency and its impact on the transformation of the environment into a more humane urban environment. The research is a survey in which, for data gathering, a questionnaire with different images of the study area has been distributed among the selected statistical population. The findings indicate that the vitality and subjective image's of citizens are directly related, and the amount of lighting and its color and the way of lighting have a positive effect on urban nightlife.